Development of Project-Based Worksheets integrated with Geogebra - Wahyuni, Yusri; Fauziah, Fauziah; Amelia, Riska; Laoli, Friska Murni Kasih (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to develop project-based student worksheets with the help of Geogebra that meet the criteria of being valid, practical and effective for students in the mathematics education study program at Bung Hatta University. This research is development research that uses the ADDIE development model with the steps, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects involved 14 students in the 6th semester of the mathematics education study program. The instruments used in the research included validity questionnaires, practicality and effectiveness tests on student worksheets. Data analysis was carried out by calculating the average expert validation score and the average score of the student response questionnaire. Meanwhile, testing the instrument for testing the effectiveness of student worksheets was carried out using item analysis and internal consistency of test items. The results of data analysis show that the student worksheets developed are in the valid category with an average level of 82%, practical with an average of 81.25%, and effective with an average of 81%. Thus, it can be concluded that the project-based student worksheets assisted by Geogebra are in the valid, practical and effective category for use in the learning process by students. Keywords: Lembar Kerja Mahasiswa, Proyek, Geogebra Abstrak: Penelitian ini bertujuan untuk mengembangkan lembar kerja mahasiswa berbasis proyek dengan bantuan geogebra yang memenuhi kriteria valid, praktis dan efektif untuk mahasiswa program studi pendidikan matematika di Universitas Bung Hatta. Penelitian ini adalah penelitian pengembangan yang menggunakan model pengembangan ADDIE dengan langkah-langkah yaitu Analysis, Design, Development, Implementation, dan Evaluation. Subjek penelitian melibatkan 14 mahasiswa semester 6 program studi pendidikan matematika. Instrumen yang digunakan dalam penelitian meliputi angket validitas, praktikalitas, dan tes efektivitas lembar kerja mahasiswa. Analisis data dilakukan dengan menghitung rata-rata skor validasi ahli dan skor rata-rata angket respon mahasiswa. Sedangkan ujicoba instrument test efektivitas lembar kerja mahasiswa dilakukan dengan analisis butir dan konsistensi internal butir tes. Hasil analisis data menunjukkan bahwa lembar kerja mahasiswa yang dikembangkan memiliki kategori valid dengan tingkat rata-rata sebesar 82%, dikategorikan praktis dengan rata-rata sebesar 81,25%, dan efektif dengan rata-rata sebesar 81%. Dengan demikian dapat disimpulkan bahwa lembar kerja mahasiswa berbasis proyek berbantuan geogebra berada pada kategori valid, praktis, dan efektif digunakan dalam proses pembelajaran oleh mahasiswa.  Kata kunci: lembar kerja mahasiswa, proyek, geogebra DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp699-709